Recombinant Alpha, Beta, and Epsilon Toxins of Clostridium perfringens: Production Strategies and Applications as Veterinary Vaccines - Ferreira, Marcos Roberto A. (Toxins (Basel), 2016)
Clostridium perfringens is a spore-forming, commensal, ubiquitous bacterium that is present in the gastrointestinal tract of healthy humans and animals. This bacterium produces up to 18 toxins. The species is classified into five toxinotypes (A–E) according to the toxins that the bacterium produces: alpha, beta, epsilon, or iota. Each of these toxinotypes is associated with myriad different, frequently fatal, illnesses that affect a range of farm animals and humans. Alpha, beta, and epsilon toxins are the main causes of disease. Vaccinations that generate neutralizing antibodies are the most common prophylactic measures that are currently in use. These vaccines consist of toxoids that are obtained from C. perfringens cultures. Recombinant vaccines offer several advantages over conventional toxoids, especially in terms of the production process. As such, they are steadily gaining ground as a promising vaccination solution. This review discusses the main strategies that are currently used to produce recombinant vaccines containing alpha, beta, and epsilon toxins of C. perfringens, as well as the potential application of these molecules as vaccines for mammalian livestock animals.